Comparison of the Sensitivity and Specificity of Tzanck Smear and Immunofluorescence Assay for the Diagnosis of Cutaneous Herpes Simplex Virus and Varicella Zoster Virus Infections in a Real-life Clinical Setting - Chayada Chaiyabutr (2022)
Objective: This research aims to compare (1) the sensitivity and specificity of Tzanck smear and indirect immunofluorescence assay (IFA) which detect viral antigen for the diagnosis of cutaneous herpes simplex virus (HSV) and varicella zoster virus (VZV) infections; and (2) the detection rates of the tests among various patient groups and lesion morphologies. Materials and Methods: This retrospective study reviewed 440 and 172 samples from patients with clinically suspicious cutaneous HSV and VZV infections, who underwent both Tzanck smear and IFA, respectively. The gold standard of the study was defined by showing agreement of diagnostic codes between initial and subsequent visits. Results: For HSV infections, the respective sensitivity and specificity of Tzanck smear were 32.8% and 96.6% whereas those of IFA were 60.7% and 100%. As to VZV infections, the sensitivity and specificity of Tzanck smear were 54.3% and 97.8%, respectively, while the corresponding values of IFA were 71.7% and 100%. According to disease characteristics and lesion morphologies, IFA provided substantially higher ability to detect HSV than the Tzanck smear, especially in patients with immunosuppressed conditions. Tzanck smear and IFA demonstrated no statistically significant difference for early-onset VZV infections (≤ 3 days). Conclusion: The Tzanck smear and IFA had higher sensitivities for detecting VZV than HSV infections. IFA testing is recommended in patients with immunosuppressed conditions who present with suspected cutaneous HSV infection. Despite the overall sensitivity and specificity of IFA being greater than those of Tzanck smear especially in HSV infections, the latter test is comparable option for early-onset VZV infections.